2008
DOI: 10.1002/cyto.a.20532
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fibroblasts responsible for cartilage destruction in arthritis

Abstract: In the pathogenesis of rheumatoid arthritis (RA), synovial fibroblasts (SF) play a key role as they secrete distinct patterns of cytokines and express variable levels of costimulatory and adhesion molecules. The murine fibroblast cell line LS48 has been shown to be invasive in the cartilage destruction models in vivo and in vitro. The purpose of this study was to examine in detail the LS48 phenotype, to obtain a better understanding of the SF-mediated cartilage destruction in RA. The destructive fibroblasts li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…For example, an up-regulated expression of CD147 was observed in the synovial membrane [132], as well as on circulating and synovial monocytes/macrophages [149], in RA patients. Increased levels of CD147 were also reported recently on a murine synovial fibroblast cell line used for studies of cartilage invasion and destruction [150]. One might postulate that an increase in CD147 expression would enhance the interaction between leucocytes and extracellular cyclophilins, thereby promoting their recruitment.…”
Section: Cd147 and Cyclophilins Are Up-regulated In Human Inflammatorsupporting
confidence: 53%
“…For example, an up-regulated expression of CD147 was observed in the synovial membrane [132], as well as on circulating and synovial monocytes/macrophages [149], in RA patients. Increased levels of CD147 were also reported recently on a murine synovial fibroblast cell line used for studies of cartilage invasion and destruction [150]. One might postulate that an increase in CD147 expression would enhance the interaction between leucocytes and extracellular cyclophilins, thereby promoting their recruitment.…”
Section: Cd147 and Cyclophilins Are Up-regulated In Human Inflammatorsupporting
confidence: 53%
“…Since these cell lines differed in the expression of the three selected biomarkers, this experiment was used to evaluate the targeting specificity of the SERRS tags. Whereas the A431 cell line expressed EGFR, EpCAM, and CD44, the 3T3 2.2 cell line expressed CD44, but neither EGFR nor EpCAM . To ascertain the differential expression of the biomarkers in A431 and 3T3 2.2 cell lines, immunofluorescence assays were also performed with the same specific antibodies used for Au@pNIPAM microgels bioconjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Among the cell-cell contact-dependent interactions leading to T-cell activation, a role for CD154 (CD40L)-CD40 engagement has been highlighted. It has been shown that CD40 is expressed on synovial fibroblasts and destructive murine fibroblasts [ 80 , 81 ], and ligation of CD40 induces SF proliferation and up-regulation of adhesion molecules [ 68 , 69 ]. However, CD154 expression on T-cells is transient and is rapidly down-regulated after binding to CD40 [ 82 ].…”
Section: Discussionmentioning
confidence: 99%